2020
DOI: 10.3390/biom10050798
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3: Roles in Neurodevelopment, Neuroinflammation, and Behavior

Abstract: There is a plethora of evidence to suggest that Galectin-3 plays an important role in normal functions of mammalian cells, as well as in different pathogenic conditions. This review highlights recent data published by researchers, including our own team, on roles of Galectin-3 in the nervous system. Here, we discuss the roles of Galectin-3 in brain development, its roles in glial cells, as well as the interactions of glial cells with other neural and invading cells in pathological conditions. Galectin-3 plays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 143 publications
(192 reference statements)
0
31
0
Order By: Relevance
“…Galectins consist of evolutionarily highly conserved carbohydrate-recognition domains (CRDs) containing approximately 130 amino acid sequences that bind β-galactose in glycoconjugates [ 13 ]. In mammalian tissues, a total of 15 galectins have been identified to date, and they have been subdivided into three subtypes according to their structures [ 5 , 14 ]: the prototype galectins include the largest number of subgroups and contain a single CRD; the chimaera-type galectins contain a single CRD and an intrinsically disordered sequence at the N-terminal domain that promotes oligomerization; and the tandem-repeat type galectins consist of two CRD motifs (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Galectins consist of evolutionarily highly conserved carbohydrate-recognition domains (CRDs) containing approximately 130 amino acid sequences that bind β-galactose in glycoconjugates [ 13 ]. In mammalian tissues, a total of 15 galectins have been identified to date, and they have been subdivided into three subtypes according to their structures [ 5 , 14 ]: the prototype galectins include the largest number of subgroups and contain a single CRD; the chimaera-type galectins contain a single CRD and an intrinsically disordered sequence at the N-terminal domain that promotes oligomerization; and the tandem-repeat type galectins consist of two CRD motifs (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…For example, a small molecule inhibitor, 33DFTG, has been shown to diminish pathological corneal neovascularization and fibrosis in experimental models. TD139 is another important Gal‐3 inhibitor in advanced phases of the clinical trial for lung fibrosis 8 . Gal‐3 inhibitors have been developed as new agents to offset lung fibrosis and hinder cancer metastasis.…”
Section: Figurementioning
confidence: 99%
“…Siew et al showed that plasma levels of Gal‐3 correlate with the severity of the Huntington's disease. Also, post‐mortem study of Huntington's disease brains revealed upregulation of Gal‐3 in the caudate‐putamen 8,17 …”
Section: Figurementioning
confidence: 99%
“…Finally, the authors concluded that gal-3 release in the central and peripheral 7 Journal of Immunology Research nervous systems would be directly related to intestinal neuronal death via toll-like receptor 4, an innate immunity receptor previously related to death induction in neurons [193]. Future studies need to focus on identifying gal-3 inhibitors for the control and treatment of CNS neuroinflammatory pathologies [194]. Thus, the use and search for these inhibitors may also represent alternatives for ENS-related diseases such as Chagasic megacolon.…”
Section: Journal Of Immunology Researchmentioning
confidence: 99%